Case Report: Hidden in motion: a challenging aortic mass unveiled by 3D transesophageal echocardiography - Malaguti, Mattia; Gerra, Luigi; Fontanesi, Leonardo; Barbieri, Andrea; Boriani, Giuseppe; Mantovani, Francesca (Frontiers in Cardiovascular Medicine, 2025)
This case report describes a 76-year-old asymptomatic male with a highly mobile, elongated, and filamentous structure incidentally detected in the ascending aorta during routine echocardiographic evaluation. The nature of this mass was initially unclear, as its appearance and behavior did not fit the typical features of thrombi, atheroma, vegetations, or dissection. Given the high risk of systemic embolization, timely intervention was deemed necessary. Advanced multimodality imaging, particularly three-dimensional transesophageal echocardiography (3D-TEE), played a pivotal role in defining the lesion's characteristics. Surgical removal was performed, and histopathological analysis provided an unexpected final diagnosis. This case underscores the value of 3D-TEE in assessing rare aortic abnormalities that may not be fully characterized using conventional imaging techniques.